Sunni-Shia Ecumenism in Austria: A Model for Western Europe? - Asfa Widiyanto (Al-Jami'ah: Journal of Islamic Studies, 2018)
The dynamics of encounter between Shiism and Sunnism have been investigated by some scholars, nevertheless the detailed study on the ventures of Sunni-Shia convergence which takes place in Austria is still underdeveloped. Such a picture is significance in revealing the features of Sunni-Shia ecumenism and its relationship with ‘European Islam’. This paper investigates the problems and the prospects for Sunni-Shia rapprochement in Austria, as well as the extent to which ecumenism in this country could serve as a model for Western Europe. The conflicts between Sunnites and Shiites are in some ways grounded in the misunderstandings between these two main sects of Islam. The recognition of faith community plays a part in figuring the fate of rapprochement between Sunnites and Shiites in the country. The prospects for Sunni-Shia ecumenism in Austria lie in the hands of authoritative personages and organisations, and in the ability of various elements of the society to enter into a dialogue to eradicate misunderstandings and prejudices. The authentic elaboration of ‘European Islam’ will also mould the future of Sunni-Shia ecumenism in Austria. There are possibilities and limits of applying Austrian model of Sunni-Shia ecumenism to other countries in Western Europe.[Dinamika perjumpaan antara Sunni dengan Syiah telah diteliti oleh banyak ahli, meskipun demikian kajian khusus tentang hubungan Sunni – Shiah  dengan studi kasus di Austria masih belum banyak diteliti. Gambarannya terletak pada arti penting pemahaman prinsipil antara Sunni – Syiah dan keterhubungan mereka dengan Islam Eropa. Tulisan ini menjelaskan berbagai persoalan dan prospek dalam membangun kedekatan keduanya di Austria sebagaimana kelanjutan perihal keyakinan di Negara tersebut sebagai model untuk Eropa Barat. Konflik antar pengikut Sunni - Syiah diantaranya mengakar karena ketidaksepahaman antar dua kelompok ini. Pengakuan komunitas agama berperan dalam penentuan pemulihan hubungan antara Sunni dan Syiah di negara ini. Prospek ekumenisme Sunni-Syiah di Austria ada di tangan tokoh dan organisasi kompeten, dan kemampuan beberapa pihak masyarakat untuk berdialog sehingga dapat menghilangkan kesalahpahaman dan prasangka. Elaborasi otentik ‘Islam Eropa’ juga akan membentuk masa depan ekumenisme Sunni-Syiah di Austria. Termasuk adanya kemungkinan dan batasan penerapan model ekumenisme Sunni-Syiah Austria ke negara-negara lain di Eropa Barat.]